2014
DOI: 10.1002/cpa.21547
|View full text |Cite
|
Sign up to set email alerts
|

Singular Value Decomposition of a Finite Hilbert Transform Defined on Several Intervals and the Interior Problem of Tomography: The Riemann‐Hilbert Problem Approach

Abstract: We study the asymptotics of singular values and singular functions of a Finite Hilbert transform (FHT), which is defined on several intervals. Transforms of this kind arise in the study of the interior problem of tomography. We suggest a novel approach based on the technique of the matrix RiemannHilbert problem and the steepest descent method of Deift-Zhou. We obtain a family of matrix RHPs depending on the spectral parameter λ and show that the singular values of the FHT coincide with the values of λ for whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(103 citation statements)
references
References 32 publications
1
102
0
Order By: Relevance
“…In [BKT13] it is shown that the asymptotic approximations to the exact singular functions f n are valid uniformly on compact subsets of the interior of I i as n → ∞. In Section 4 we show that these approximations are also valid in the L 2 (I i ) sense as well.…”
Section: −1mentioning
confidence: 87%
See 4 more Smart Citations
“…In [BKT13] it is shown that the asymptotic approximations to the exact singular functions f n are valid uniformly on compact subsets of the interior of I i as n → ∞. In Section 4 we show that these approximations are also valid in the L 2 (I i ) sense as well.…”
Section: −1mentioning
confidence: 87%
“…We do not consider the other set of singular functions that are defined on I e , since they are not needed for the analytic continuation of ψ. The main idea of the approach in [BKT13] is to reduce the SVD problem (1.9) to a matrix Riemann-Hilbert problem (RHP), which, in turn, is asymptotically reduced to a simpler RHP. That simpler (model) RHP has an explicit solution, which can be expressed in terms of the Riemann Theta function.…”
Section: −1mentioning
confidence: 99%
See 3 more Smart Citations